Interventions to enhance access to and utilization of formal community care services for home dwelling persons with dementia and their informal carers. A scoping review. (1st February 2020) - Røsvik, Janne; Michelet, Mona; Engedal, Knut; Bieber, Anja; Broda, Anja; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Meyer, Gabriele; Marques, Maria J.; et al.
Abstract: Objectives: Home dwelling people with dementia and their informal carers often do not receive the formal care services they need. This study examined and mapped the research regarding interventions to improve access and use of formal community care services. Method: This is a scoping review with searches in PubMed, CINAHL, PsychINFO, Medline, Cochrane Database of Systematic Reviews, Social Science Citation index and searches of grey literature in international and national databases. Studies were categorized according to the measure used to enhance access or use. Results: From international databases, 2833 studies were retrieved, 11 were included. Five studies were included from other sources. In total, 16 studies published between 1989 and 2018 were examined; seven randomized controlled trials, six pretest-posttest studies and three non-randomized controlled studies. Sample sizes varied from 29 to 2682 participants, follow-up from four weeks to four years. Five types of interventions were identified: Case management, monetary support, referral enhancing, awareness & information focused and inpatient focused. Only two studies had access or use of community services as the primary outcome. Fourteen studies, representing all five types of interventions, had positive effects on one or more relevant outcomes. Two interventions had no effect on relevant outcomes. Conclusion: The included studies varied widely regarding design, type of intervention and outcomes. Based on this, the evidence base for interventions to enhance access to and use of formal community services is judged to be limited. The most studied type of intervention was case management. More research is recommended in this field.